Implementation and building of cheaper signal conditioners & a PID controller block using a PLC - Ndhlovu, Archiford (Midlands State University, 2019)
The proportional, integral and derivative (PID) technique is a reliable and widely used art to control and regulate complex processes. The PID block and signal conditioners are constructed by hand inside a small memory Schneider PLC without inbuilt process control loops using software. Analogue input module of the PLC receives the analogue unconditioned signal from the rtd/thermocouple sensor, passes it through the signal conditioning phase to the pid block. The PID block executes the control logic with two degrees of freedom and then sends it to the output signal conditioning block then output PLC output module. Signal conditioning is done between the input module interface & the PID block module and also between the PID block and the output module. The processed output signal shall be sent to the final control element with the use of the PWM technique. Precise temperature control is difficult to achieve using simple inexpensive techniques, it can easily be achieved by using highly sophisticated expensive PLCs that come with inbuilt process control loops. This project aims to show that with great ingenuity, cheaper PLCs without inbuilt process control loops can be equally used to precisely control complex processes by manually building PID control blocks and signal conditioners.